Lateral lumbar interbody fusion with unilateral pedicle screw fixation for the treatment of adjacent segment disease: a preliminary report - Du, Jerry Y.; Kiely, Paul D.; Al-Maaieh, Motasem; Aichmair, Alexander; Huang, Russel C. (Journal of Spine Surgery, 2017)
Background: To assess the clinical outcomes of 20 patients who underwent single level unilateral pedicle screw fixation following lateral lumbar interbody fusion (LLIF) for treatment of lumbar adjacent segment disease (ASD). Methods: Demographic, comorbidity, clinical assessment, peri-operative, and complication data were assessed. Visual analog scale (VAS), Oswestry disability index (ODI), and short form-12 (SF-12) were used to assess clinical outcomes. Post-operative radiographs were assessed for subsidence, cage migration, and fusion. Results: Average age of patients was 63.2±13.7 years (range, 41–86 years), with 8 males and 12 females. Recombinant human bone morphogenic protein-2 (rhBMP-2) was utilized in 18 LLIF cages (90%) and 12 posterolateral fusions (60%). Mean operation time was 214.1±47.2 minutes (range, 146–342 minutes), mean estimated blood loss of 187.5±90.1 cc (range, 50–400 cc). No patients received a blood transfusion. There were no intra-operative complications. Mean hospital length of stay was 4.4±1.7 days (range, 2–9 days). At final follow-up (mean: 13.0±12.7 months after surgery), there was significant improvement in post-op VAS (P=0.006) score compared to pre-op, but not ODI (P=0.181), SF-12 PC (P=0.480), and SF-12 MC (P=0.937). Patients with >6 months of post-operative imaging (14/20, 70%) demonstrated successful fusion in 13 out of 14 cases (93%). There was grade 0 subsidence of adjacent cranial vertebra in all cases (100%). There was grade 0 subsidence of the adjacent caudal vertebra in 13 cases (93%) and grade 1 subsidence in 1 case (7%). There was evidence of cage migration in 3 cases (21%). There were 4 patients (20%) who experienced transient neurological deficits that eventually resolved. Two patients required surgery for further ASD. Conclusions: In conclusion, this pilot study suggests that patients who undergo LLIF with unilateral pedicle screw fixation for treatment of ASD may have significantly reduced pain and favorable radiographic results. Further investigation in techniques for treatment of ASD is warranted.